De Geschreven Stad. - Dewilde, Michel (Brugge : Cultuurcentrum Brugge, 2015)
Becker, Lutz ; Budsynnski, Marek ; El Lissitzky ; Dale, Tom ; Bertelli, Renato ; Vahabzadeh, Tala ; Meuris, Wesley ; Milner, Henry ; Siti, Walid ; Grootjans, Loek ; Delvoye, Wim ; Mousavi, Mir Hossein ; Milner, Henry ; Cherri, ALi ; Baalbaki, Ayman ; Beuys, Joseph ; Lopez-Menchero, Emilio ; Norman, Nils ; Saadeh, Raeda ; Harb, Hazem ; Mellaerts, Hugo ; Potrc, Marjetica ; Menia, Amina ; Pope.L, William ; Basmazölmez, Ragip ; Abu Hamdan, Lawrence ; Hamadeh, Rana ; McGill, Dominic
De Geschreven Stad / The Written City, Triennale Brugge, 20 May - 18 October 2015
kunstcatalogus